JUVENILE RHEUMATOID ARTHRITIS - Sartika, I N; Santoso, Hendra; Kumara Wati, Dewi (Medicina; Vol 39 No 1 (2008): Januari 2008, 2012)
Juvenile rheumatoid arthritis (JRA) is the most common rheumatic condition in children. JRA is defined as persistent arthritis in 1 or more joints for at least 6 weeks, with the onset before age 16 years. The etiology of JRA is unknown. Antigen activated CD4+ T cell stimulate monocytes, macrophages, and synovial fibroblasts to produce the cytokines Interleukin-1 (IL-1), IL-6, and tumor necrosis factor ? (TNF-?) and to secrete matrix metalloproteinases, which lead to chronic inflammation due to infiltration of inflammatory cell, angiogenesis, destruction of cartilage and bone with pannus formation. The 3 major subtypes of JRA are based on the symptoms at disease onset and are designated systemic onset, pauciarticular onset, and polyarticular onset. For all patients, the goals of therapy are to decrease chronic joint pain and suppress the inflammatory process. Poor prognostic have been observed in patients with polyarticular onset, rheumatoid factor, persistent morning stiffness, tenosynovitis, involvement of the small joints, rapid appearance of erosions, active late onset childhood, subcutaneous nodules, or antinuclear antibody.
Keywords: rheumatoid arthritis, inflammation, antirheumatic agents